1998
DOI: 10.1097/00006123-199808000-00073
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Epidural Pressure Measurement in Clinical Practice: Behavior of Three Modern Sensors during Simultaneous Ipsilateral Intraventricular or Intraparenchymal Pressure Measurement

Abstract: The reliability of EDP measurement has not improved, compared with 10 years ago. Using this technique, one must be aware of the possibility of overestimating intracranial pressure by more than 10 mm Hg and the possibility of significant drifting of EDP over time, which argues against the use of this method even for trend analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…It is well known that ICP values obtained from the epidural compartment may be artifactually higher than those obtained in other craniospinal compartments (7,9,13,30,35,37). Nevertheless, in a stable patient, changes in ICP and qualitative information (graphic ICP recordings) are absolutely parallel and can be used interchangeably in some types of patients (13,30,35,37).…”
Section: Influence Of Epidural Monitoring On Icp Gradientsmentioning
confidence: 99%
“…It is well known that ICP values obtained from the epidural compartment may be artifactually higher than those obtained in other craniospinal compartments (7,9,13,30,35,37). Nevertheless, in a stable patient, changes in ICP and qualitative information (graphic ICP recordings) are absolutely parallel and can be used interchangeably in some types of patients (13,30,35,37).…”
Section: Influence Of Epidural Monitoring On Icp Gradientsmentioning
confidence: 99%
“…Raabe et al 20 also described this latency. The authors conclu ded that these drifting periods could be found during throu ghout the entire measurement.…”
mentioning
confidence: 82%
“…The authors conclu ded that these drifting periods could be found during throu ghout the entire measurement. The biomechanical conditions in the epidural space can influence pressure distribution to the sensor and interfere with epidural pressure system measurements 16,20 . The model described here seems useful for understan ding some important pathophysiological characteristics of acute IH.…”
mentioning
confidence: 99%
“…In den letzten Jahren haben sich insbesondere die Methoden der intraparenchymalen und intraventrikulären ICP-Messung gegenüber der epiduralen und subduralen/subarachnoidalen Messung durchgesetzt. Zwar ist die epidurale ICP-Messung als ¹weniger invasivª anzusehen, da die Dura mater unverletzt bleibt, jedoch ist sie im Hinblick auf die Qualität der Messung der intraparenchymalen und intraventrikulären Messung deutlich unterlegen [6,7]. Tab.…”
Section: Monitoring Des Intrakraniellen Drucksunclassified